Laboratory investigation of the increased content of aged SBS modified asphalt attributable to the warm-mixed recycled technology. (2nd January 2023) - Qiu, Ke; Li, Bo; Nan, Xueli; Li, Xiaomin; Chen, Jiangcai; Li, Andi; Li, Zhiwei
Highlights: Regenerated technology can increase the content of aged SBSMA by approximately about 30%. Warm-mixed recycled technology can increase aged SBSMA's content by approximately 50%. The increased content of aged SBSMA damages regenerated and warm-mixed recycled SBSMA's high-temperature properties. The fatigue performance of regenerated and warm-mixed recycled SBSMA reaches its peak value with 40% of aged SBSMA. Abstract: It has been proven that warm-mixed recycled technology (WMRT) can increase the content of aged asphalt. Until now, it is hard to describe the increased value of the content of aged SBS modified asphalt (SBSMA) because of the addition of the regeneration agent and warm mix additive quantitatively. SBSMA with or without regeneration agents, and warm-mixed recycled SBSMA were prepared in the laboratory. Brookfield rotational viscosity tests, Dynamic shear rheological tests, and Force-ductility tests were performed to evaluate the effect of different percentages of aged SBSMA on viscosity-temperature performance, rutting resistance, fatigue resistance, and low-temperature cracking performance. The increased value of the content of aged SBSMA attributable to the addition of warm mix additive or a regeneration agent was determined according to various climate zones using analysis the hierarchical process. The results illustrated that regenerated technology could increase the content of aged SBSMA by approximately 30%, and WMRT increased its content by approximately 50%, which were calculated from the analytic hierarchy process. The increased value of the content varied with the change in ambient temperature. The high-temperature performance of warm-mixed recycled SBSMA decreased as the content of aged SBSMA increased. This was an unexpected change that could be attributed to the regeneration agent's interaction of with the aged SBS. The high-temperature performance of regenerated asphalt with a regeneration agent weakened, but the low-temperature performance increased. The fatigue performance of the regenerated asphalt with regeneration agents and warm-mixed recycled asphalt reached its peak value when the content of aged SBSMA was 40%, while the low-temperature performance of warm-mixed recycled SBSMA deteriorated as the proportion of aged SBSMA increased. The wax-based warm mix additive played a major role in increasing high-temperature and fatigue performance, but reduced to low-temperature performance.